Pengaruh Country Of Origin dan Motivasi Konsumen Terhadap Keputusan Pembelian Produk Sepatu Sneakers Brand Lokal - Hanifia Syahana; Netti Nurlenawati; Dexi Triadinda (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Fashion trends that develop every year create different consumer behavior every year. Sneakers, which are included in fashion, are currently increasing their market expansion. The researcher's aim is to find out how much influence country of origin and consumer motivation have on purchasing decisions for local brand sneakers, quantitative methods with descriptive and verification are used in this study. This study applies purposive sampling techniques from a specific population. The Hair et all formula is used as a formula for calculating the sample size. The SPSS application is used by researchers as a multiple linear regression analysis tool. The final results of this study are shown by the country of origin variable which has a positive and significant effect on purchasing decisions and the same is the case with the consumer motivation variable which has a positive and significant effect on purchasing decisions. The results of this research show that the variables of country of origin and consumer motivation simultaneously have a positive and significant influence on purchasing decisions.